If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1(4x + -6) = 6x + 38 Reorder the terms: 2x + -1(-6 + 4x) = 6x + 38 2x + (-6 * -1 + 4x * -1) = 6x + 38 2x + (6 + -4x) = 6x + 38 Reorder the terms: 6 + 2x + -4x = 6x + 38 Combine like terms: 2x + -4x = -2x 6 + -2x = 6x + 38 Reorder the terms: 6 + -2x = 38 + 6x Solving 6 + -2x = 38 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 6 + -2x + -6x = 38 + 6x + -6x Combine like terms: -2x + -6x = -8x 6 + -8x = 38 + 6x + -6x Combine like terms: 6x + -6x = 0 6 + -8x = 38 + 0 6 + -8x = 38 Add '-6' to each side of the equation. 6 + -6 + -8x = 38 + -6 Combine like terms: 6 + -6 = 0 0 + -8x = 38 + -6 -8x = 38 + -6 Combine like terms: 38 + -6 = 32 -8x = 32 Divide each side by '-8'. x = -4 Simplifying x = -4
| 4y+12=-1/3(8-12y) | | 9/11*14.4 | | z/4+6=8-z/4 | | C-3/16=-5 | | 1r+2s+6r+-1s= | | x/2-34=55 | | 3.50x+5.50x-6=51 | | -4-4x=-2x-4 | | 72/12 | | 3x-5(x-2)=-7+2x-7 | | 5(x+2)+(8x+24)=-1.75 | | z^2-z=90 | | y/2+x | | z/2+6=7-z/2 | | 86/12 | | 5-6(2+b)=6-14 | | .5x-3=.5 | | 5x+28=8x+10 | | 7r-6s+2r+3s= | | 6n+8-2n=-8 | | 5x^2+8=-12x | | 4+2x=4x-2 | | 8k-1=25 | | 1/7(14+28)=2(r+2) | | 3.4(-3.8z+1.2b-3.3)= | | 7/98 | | 987whcsdg=7 | | 5s-r+7r-6s= | | x/4+6=x+12 | | 51.56-29.28x=47.78-68.82 | | 9xd=4 | | 1x+1=1x-1 |